On the investigation of cracking phenomena of plasma spray zirconia coating with new information and understanding - Akira, Kobayashi; Al-Shamrani, Mosleh; El-Sheikhy, Refat (Penerbit UTM Press, 2015)
Phenomena of Zr coating cracking were studied. It concentrates on developing of a new theory of zirconia cracks and a new modeling system in addition to the fundamental analysis. These previous studies could not solve all the aspects of that complicated problem of Zr cracking while in current study a new modeling was proposed for the Zr coating layers and crack as modification and development with new information and new understanding. Analytical study with fundemantal results regarding the mechanism, loads and behavior under triaxil thermal stresses interaction of both high thermal plasma on outer face and high cooling on the backside of the substrate. Results are new, useful and interesting.